2020
DOI: 10.1051/e3sconf/202019000016
|View full text |Cite
|
Sign up to set email alerts
|

Performance Study of Maximum Power Point Tracking (MPPT) Based on Type-2 Fuzzy Logic Controller on Active Dual Axis Solar Tracker

Abstract: World energy consumption increases with time, so that occur an energy imbalance. Many breakthroughs have developed to utilize renewable energy. The photovoltaic system is one of the easy-to-use renewable energies. The power conversion from PV fixed is still low, so the PV system is designed using the active dual-axis solar tracker. The PV tracker position can be adjusted to change the sun position to get maximum efficiency. The active dual-axis solar tracker system is integrated with the maximum power point tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As a result of this modification, the solar panel receives more sunlight, resulting in a higher output voltage value than the static mode solar panel used for comparison. Other research has found that utilizing solar trackers can improve the effectiveness of absorbing thermal energy from the sun [1,14,15].…”
Section: Comparison Of the Output Voltage Of A Solar Cell Using A Sol...mentioning
confidence: 99%
“…As a result of this modification, the solar panel receives more sunlight, resulting in a higher output voltage value than the static mode solar panel used for comparison. Other research has found that utilizing solar trackers can improve the effectiveness of absorbing thermal energy from the sun [1,14,15].…”
Section: Comparison Of the Output Voltage Of A Solar Cell Using A Sol...mentioning
confidence: 99%
“…By changing the voltage input values, we obtained the required levels. Figure (12), shows the connection of four solar cells with voltage regulators and a multi-level inverter. The MLI has several advantages over a typical inverter, including lower harmonics and higher output voltages, as well as lower cost and superior efficiency.…”
Section: Figure (11): Gate Drive Circuit Tlp 250 Optocouplermentioning
confidence: 99%
“…This useful innovation to take advantage of this energy potential presents a In operation, the performance of PV depends on temperature and exposure to irradiation, so these two parameters are the main factors affecting the power yield obtained [4]. In the next development, PV which was added by electronic devices presented a more sophisticated technology, namely the solar tracker [5]. The system configuration uses a light dependent resistor (LDR) sensor and an actuator in the form of a DC motor [6], [7].…”
Section: Introductionmentioning
confidence: 99%